2011
DOI: 10.3310/hta15100
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept, infliximab and adalimumab for the treatment of psoriatic arthritis: a systematic review and economic evaluation

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(164 citation statements)
references
References 175 publications
5
155
0
4
Order By: Relevance
“…In the present study, the efficacy of the TNF-α inhibitors etanercept and infliximab in plaque psoriasis therapy has been clearly demonstrated, in agreement with previous studies (2)(3)(4)(5)(6). Furthermore, concerning the small number of infliximab-treated cases or female patients, this study revealed notable observations regarding correlations among pro-inflammatory genes, anti-TNF-α treatment type and gender.…”
Section: A B C Dsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the efficacy of the TNF-α inhibitors etanercept and infliximab in plaque psoriasis therapy has been clearly demonstrated, in agreement with previous studies (2)(3)(4)(5)(6). Furthermore, concerning the small number of infliximab-treated cases or female patients, this study revealed notable observations regarding correlations among pro-inflammatory genes, anti-TNF-α treatment type and gender.…”
Section: A B C Dsupporting
confidence: 92%
“…Treatment of severe psoriatic plaques may involve biological agents that block the action of tumor necrosis factor (TNF)-α, such as etanercept and infliximab (2)(3)(4)(5)(6). Etanercept is a recombinant human TNF-receptor fusion protein that binds free TNF-α (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Review of the natural history of psoriatic arthritis: registry and cohort study data A total of four publications 33,[98][99][100] analysing patterns of natural disease progression in registries or long-term cohort data were found and are shown in Table 36. These were reviewed in order to gain an understanding of the manner in which disease progresses in patients who do not receive anti-TNF therapy, despite being eligible for treatment.…”
Section: Effect Of Anti-tumour Necrosis Factors On Radiographic Progrmentioning
confidence: 99%
“…Owing to the now ubiquitous nature of anti-TNFs and only recent recognition of PsA as a separate and distinct form of arthritis, information on the long-term uncontrolled progression of the disease is scarce. Two of the studies 33,100 found in the literature search were different analyses of the same data set derived from the Norfolk Arthritis Register (NOAR): one was a 2-year prospective cohort study 99 and the other a retrospective analysis of a Canadian single-site patient registry. 98 The studies explore changes in functional disability in terms of HAQ-DI score and bone erosion as measures of disease activity and progression over time.…”
Section: Effect Of Anti-tumour Necrosis Factors On Radiographic Progrmentioning
confidence: 99%
See 1 more Smart Citation